Klippel-Feil Syndrome (Type I) and Disc Cervical Extrusion in a Dog - de Siqueira, Emerson Gonçalves Martins; Guimarães, Fernanda Catacci; Rahal, Sheila Canevese; Maciel, Luigi Milanez Àvila Dias; de Vasconcelos Machado, Vania Maria; Bazan, Rodrigo; Hamamoto Filho, Pedro Tadao; Abibe, Rebeca Bastos (Acta Scientiae Veterinariae, 2024)
Background: Klippel-Feil Syndrome (KFS) is a rare diagnosed condition in human and animals. They are usually asymptomatic and considered a clinical finding after image exam due to another neurological sign. This syndrome can be classified in Type I, Type II or Type III. The immobile neck may cause a biomechanical change in the spine motion and predispose disc herniation. This case aims to report a case of a dog with diagnosed KFS with disc extrusion, its treatment and follow up. Case: A 8‐year‐old entire male Dachshund was referred for evaluation because of a history of chronic cervical kyphosis and low head carriage, and a 7-day history of acute onset of non-ambulatory spastic tetraparesis and neck pain without improvement after clinical treatment with non-steroidal anti-inflammatory and analgesic. Blood and white cell count were within the normal range, as vital parameters. Cranial nerves were considered normal and no brain disorder was observed during physical examination, only aggressive behavior after management related to pain. Hyperreflexia and hypertonia were observed in all 4 limbs, with cervical painful cervical flexion and turning. Plain radiographs of the cervical spine revealed fusion of the vertebral bodies of C2 and C3, and calcification of the intervertebral disc at C5-C6, with mild narrowing of the disc space. MRI revealed fusion between C2-C3 with an absence of the intervertebral disc, and changes in the signal intensity of the spinal cord were not identified at the malformation site. In the ventral aspect of the spinal canal dorsal to C5-C6 disc space, there was T2 hypointense material consistent with herniated intervertebral disc material, causing extra-dural spinal cord compression. The diagnosis was Klippel-Feil syndrome (Type I) at C2-C3 and disc extrusion at C5-C6. A ventral slot decompression surgery was performed between C5-C6, the intervertebral space was identified based on palpation of the transverse process of C6. On the day after the surgery the patient displayed a neurological improvement with ambulatory spastic tetraparesis, and on the 5th day the dog was able to get up and walk without ataxia and neck pain. At the final evaluation, 1.6 years after the surgery, the dog was neurologically normal. Discussion: Due to its common undiagnosed frequency in veterinary medicine, this case report presents a diagnosed Klippel-Feil syndrome (KFS) with disc extrusion in a dog. Corroborating with usual findings in this syndrome, this patient presented short neck and limited neck range of motion in flexion and extension. The low posterior hairline was mild. KFS may be find occurring with intervertebral disc disease in consequence of the change in the spine’s range of motion. Other abnormalities have been associated in human KFS, such as scoliosis, rib deformity, deafness and systemic disorders as renal and cardiovascular. The patient in this case report presented any systemic injury possible to relate with the KFS. The gold standard diagnostic method is magnetic resonance image (MRI), but a gross evaluation can be made in the simple x-ray. Surgical treatment is not necessary when KFS is asymptomatic. Disc extrusion is associated to possible stress on normal intervertebral disc due to decreased mobility in the fused cervical segment. Ventral slot was performed in the C5-C6 disc extrusion to spinal cord decompression, the location corroborates with usual site of intervertebral disc disease. During the follow up (> 1 year), the patient maintained itself neurologically normal. This case report raises the importance to identify KFS in veterinary medicine, which may be being under-reported and its possibility to bias degenerative disease in the intervertebral disc. Keywords: vertebrae fusion, congenital deformities, canine, KFS, IDD, ventral slot.